The Application of Asynchronous Learning for English Language Teaching in English and Non-English Study Program - Dhion Meitreya Vidhiasi; Mohammad Andi Hakim; Ana Humardhiana; Listiana Ikawati; Muhsiyanah Nurul Aisyiyah (Journal of English as A Foreign Language Teaching and Research, 2021)
The condition of the COVID19 pandemic has changed the habits of the world, including the education sector in Indonesia. For schools with strong economic strength, both students and educators will have no significant difficulties in implementing face-to-face online learning in a full manner (synchronous). On the other hand, there are many obstacles to implementing synchronous learning in schools with low economic abilities for both students and educators. One learning method that can be done with minimal barriers is asynchronous learning. Akademi Maritim Nusantara Cilacap and IAIN Syekh Nurjati Cirebon, both schools have low economic strength, both students and lecturers. This study aims to see the benefits and problems that arise in applying asynchronous learning in Maritime English II of Akademi Maritim Nusantara Cilacap and English I of IAIN Syekh Nurjati Cirebon course. The researcher uses Google Classroom, YouTube, WhatsApp and Telegram media in lecture activities. The researcher then conducted a mini-survey to find out the advantages and obstacles experienced by students. The data is then explained using a qualitative descriptive method. The results showed at least 5 (five) advantages and 1 (one) weakness in asynchronous learning. The five benefits are material enrichment, access to learning materials, social interaction, personal interaction, and ease in discussing student work. Meanwhile, the constraints found were related to cost-effectiveness.